Esophageal perforation in children: etiology and management, with special reference to endoscopic esophageal perforation - Krishna Kumar Govindarajan (Korean Pediatric Society, 2018)
Perforation of the esophagus is an uncommon problem with significant morbidity and mortality. In children undergoing endoscopy, the risk of perforation is higher when interventional endoscopy is performed. The clinical features depend upon the site of esophageal perforation. Opinions vary regarding the optimal treatment protocol, and the role of conservative management in this context is not well established. Esophageal perforation that occurs as a consequence of endoscopy in children requires careful evaluation and management, as outlined in this article.